2017
DOI: 10.1159/000478782
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Volatile Organic Compounds as Potential Biomarkers in Idiopathic Membranous Nephropathy

Abstract: Objective: To detect urinary volatile organic compounds (VOCs) in patients with idiopathic membranous nephropathy (iMN) and normal controls, and to examine whether or not urinary VOCs can act as biomarkers for the diagnosis of iMN independent of renal biopsy. Materials and Methods: Gas chromatography/mass spectrometry (GC/MS) was used to assess the urine collected from 63 iMN patients and 15 normal controls. The statistical methods of principal component analysis and partial least squares discriminant analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 29 publications
(33 reference statements)
0
15
0
Order By: Relevance
“…CAN_1 variable markedly separated Y from the other three groups and the discriminant VOCs involved were 2-butanone, isopropyl alcohol, 2-pentanone, 3penten-1-ol, and pyrrole. These VOCs were detected in the urine of healthy subjects but also, in some cases with higher levels, in patients with different pathologies, such as cancer, nephropathy, and metabolic disorders (Silva et al 2012;Wang et al 2017;Mochalski et al 2018;Jia et al 2019). In our samples, these VOCs were more associated with Y group as they showed a higher correlation with CAN1.…”
Section: Discriminant Analysis Of Urinesmentioning
confidence: 48%
“…CAN_1 variable markedly separated Y from the other three groups and the discriminant VOCs involved were 2-butanone, isopropyl alcohol, 2-pentanone, 3penten-1-ol, and pyrrole. These VOCs were detected in the urine of healthy subjects but also, in some cases with higher levels, in patients with different pathologies, such as cancer, nephropathy, and metabolic disorders (Silva et al 2012;Wang et al 2017;Mochalski et al 2018;Jia et al 2019). In our samples, these VOCs were more associated with Y group as they showed a higher correlation with CAN1.…”
Section: Discriminant Analysis Of Urinesmentioning
confidence: 48%
“…As a developing novel tool for the non-invasive detection of various disease states in recent years, VOC analysis has been applied in different body fluids, such as blood, urine, and saliva [12][13][14][15]. VOC analysis is important in the diagnosis of respiratory infections as an accurate and rapid method and has clinical value in guiding the use of antibiotics [19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Among them, gas chromatography-mass spectrometry (GC-MS) is a preferred method for the identification of pathogen markers with an appropriate sensitivity [11]. As a developing novel tool for non-invasive detection of various disease states in recent years, VOC analysis has been applied in different body fluids, such as blood, urine, and saliva [12][13][14][15], and it also can be applied to identify pathogens such as Escherichia coli, Staphylococcus aureus, Mycobacterium tuberculosis, Haemophilus influenzae, Streptococcus pneumoniae, rhinoviruses, influenza A virus and others [9,10,16]. Although there are a large number of clinical studies on the diagnosis of CNS infection such as cellular and chemistry parameters in CSF, conventional culture for bacteria and PCR with sequencing for viral [3,17] studies on the VOCs in the CSF have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Urine is frequently analyzed using Liquid Chromatography-Mass Spectrometry (LC-MS), Gas Chromatography-Mass Spectrometry (GC-MS) and Nuclear Magnetic Resonance Spectroscopy (NMR) [5][6][7]. A specific class of metabolomics focused on the profile of volatile compounds (VCs) is termed volatolomics, the applications of which for diagnostic purposes is growing [8][9][10][11][12][13][14][15]. VCs are secreted by cells of the human body, as a result of their metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…The changes in the profile of VCs in biological fluids, dependent on the metabolic changes, may reflect the presence of disease. Many studies have suggested that the profile of VCs in urine change in cancer [8][9][10], nephrological conditions [15], oxidative stress [11], gastrointestinal diseases [12][13][14] and other disease states.…”
Section: Introductionmentioning
confidence: 99%